Cyclic voltammetric studies on some antioxidants with carbon paste-based and boron-doped diamond electrodes - Pekec, Bruna; Misini, Miranda; Sýs, Milan; Samphao, Anchalee; Vytřas, Karel; Ortner, Astrid; Feketeföldi, Birgit; Ribitsch, Volker; Arbneshi, Tahir; Kalcher, Kurt (Univerzita Pardubice, 2012)
Some selected antioxidants and (poly)phenolic compounds occurring as basic skeletons in antioxidants were investigated with carbon paste and boron-doped diamond electrodes using cyclic voltammetry and hydrodynamic amperometry. The results show that the doped diamond electrode provides stable and reproducible responses which can be exploited for analytical purposes whereas with carbon paste strong adsorption of phenol and hydroquinone as well as of their oxidation products occurs.
Keywords: antioxidants; hydroquinone; cyclic voltammetry; hydrodynamic amperometry; carbon paste electrode; boron-doped diamond electrode